Mengapa dunia barat kembali pada Islam - Naik, Zakir, 1965-; Ababil [Production] ([s.l.] : Ababil)
Dr. Zakir Naik talk about the reason why the foreign countries back to Islam when it is regarding social issues. Dr. Zakir Naik explained the practices of Islam based on Al-Quran where its will solve any social problems that may occured
Title from title screen
In English and subtitle in Indonesian
Penceramah: Dr. Zakir Naik
Keywords: Islam -- Customs and practices; Islam